ANALISIS UPAYA PENINGKATAN PELAYANAN PRIMA DALAM PELAYANAN PUBLIK DI BALAI DESA CANGKRINGSARI - M. Irfan Ardiyanto; Nailul Ulah Al-Chumairah Machfud (Jurnal Multidisipliner Kapalamada, 2026)
This study aims to analyze efforts to improve excellent service at Cangkringsari Village Hall and identify supporting and inhibiting factors in its implementation. This research employed a qualitative descriptive approach with a case study design. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model through data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings show that excellent service has been implemented but remains suboptimal. The tangible dimension is constrained by limited facilities, reliability by slow service completion, responsiveness by limited service personnel, assurance by uneven information technology competence, and empathy by varied quality of interpersonal attention. Supporting factors include the Village Head's commitment, district government support, and community input. Inhibiting factors include limited human resources, budget constraints, unclear standard operating procedures, and slow bureaucratic culture. The study recommends strengthening staff competence, improving facilities, formalizing SOPs, expanding digitalization, and enhancing humanistic communication.